Therapeutic touch: placebo effect or energetic form of communication. - Straneva J (Journal of Holistic Nursing, 1991)
The purpose of this paper is to consider whether Therapeutic Touch, a meditative healing technique, is a placebo or whether it is a form of communication with energetic or electrical properties. Both claims have been proposed by the technique's adherents. Peirce's theory of signs and Wilber's epistemologically-oriented, new world paradigm were used as a framework for analyzing the merits of each premise. Therapeutic Touch is evaluated in terms of six elements of communication: the source, destination, channel, message, code and context. Comparisons are supported by rational argument and research findings.